Notch Signaling Regulates Mitochondrial Metabolism and NF-κB Activity in Triple-Negative Breast Cancer Cells via IKKα-Dependent Non-canonical Pathways - Hossain, Fokhrul; Sorrentino, Claudia; Ucar, Deniz A.; Peng, Yin; Matossian, Margarite; Wyczechowska, Dorota; Crabtree, Judy; Zabaleta, Jovanny; Morello, Silvana; Del Valle, Luis; Burow, Matthew; Collins-Burow, Bridgette; et al. (Frontiers in Oncology, 2018)
Triple negative breast cancer (TNBC) patients have high risk of recurrence and metastasis, and current treatment options remain limited. Cancer stem-like cells (CSCs) have been linked to cancer initiation, progression and chemotherapy resistance. Notch signaling is a key pathway regulating TNBC CSC survival. Treatment of TNBC with PI3K or mTORC1/2 inhibitors results in drug-resistant, Notch-dependent CSC. However, downstream mechanisms and potentially druggable Notch effectors in TNBC CSCs are largely unknown. We studied the role of the AKT pathway and mitochondrial metabolism downstream of Notch signaling in TNBC CSC from cell lines representative of different TNBC molecular subtypes as well as a novel patient-derived model. We demonstrate that exposure of TNBC cells to recombinant Notch ligand Jagged1 leads to rapid AKT phosphorylation in a Notch1-dependent but RBP-Jκ independent fashion. This requires mTOR and IKKα. Jagged1 also stimulates mitochondrial respiration and fermentation in an AKT- and IKK-dependent fashion. Notch1 co-localizes with mitochondria in TNBC cells. Pharmacological inhibition of Notch cleavage by gamma secretase inhibitor PF-03084014 in combination with AKT inhibitor MK-2206 or IKK-targeted NF-κB inhibitor Bay11-7082 blocks secondary mammosphere formation from sorted CD90hi or CD44+CD24low (CSCs) cells. A TNBC patient-derived model gave comparable results. Besides mitochondrial oxidative metabolism, Jagged1 also triggers nuclear, NF-κB-dependent transcription of anti-apoptotic gene cIAP-2. This requires recruitment of Notch1, IKKα and NF-κB to the cIAP-2 promoter. Our observations support a model where Jagged1 triggers IKKα-dependent, mitochondrial and nuclear Notch1 signals that stimulate AKT phosphorylation, oxidative metabolism and transcription of survival genes in PTEN wild-type TNBC cells. These data suggest that combination treatments targeting the intersection of the Notch, AKT and NF-κB pathways have potential therapeutic applications against CSCs in TNBC cases with Notch1 and wild-type PTEN expression.